Portafolio de negocios del sector financiero formal de la ciudad de Latacunga, provincia de Cotopaxi en el año 2012-2013 - Gómez Velozo, Geovanna Paola (2014)
The aim by which the ring binder business was created from the financial sector in Latacunga city, Cotopaxi Province in the period 2012 – 2013 was present the services and products, promotions and plans that different banks, register in the Banks and Insurance Companies of Ecuador, bid in Latacunga city, analyzing the Banking and Financial System basing on the formal financial ring bind structure, so that as a methods in this investigation was used surveys and interview in order to get real information and specify that it is specified in the financial business ring bind. The proposal is contribute in a socioeconomic part in the City as foment the economic activity, imposing new entrepreneurs and creating a culture of savings and invest that goes in benefit of a common good, with a vision wide of total getting by part of the population in basis to products and services.